Optoelectrical Properties of Treated CdSe Thin Films with Variations in Indium Chloride Concentration - Nisham Rosly H.; Doroody C.; Harif M.N.; Mohamad I.S.; Isah M.; Amin N. (MDPI, 2024)
The effect of a nontoxic chloride treatment on the crystallinity and optoelectrical characteristics of a CdSe thin film was studied. A detailed comparative analysis was conducted utilizing four molarities (0.01 M, 0.10 M, 0.15 M, and 0.20 M) of indium (III) chloride (InCl3), where the results showed a notable improvement in CdSe properties. The crystallite size of treated CdSe samples increased from 31.845 nm to 38.819 nm, and the strain in treated films dropped from 4.9 10?3 to 4.0 10?3, according to XRD measurements. The highest crystallinity resulted from the 0.10 M InCl3-treated CdSe films. The In contents in the prepared samples were verified by compositional analysis, and FESEM images from treated CdSe thin films demonstrated compact and optimal grain arrangements with passivated grain boundaries, which are required for the development of a robust operational solar cell. The UV-Vis plot, similarly, showed that the samples were darkened after treatment and the band gap of 1.7 eV for the as-grown samples fell to roughly 1.5 eV. Furthermore, the Hall effect results suggested that the carrier concentration increased by one order of magnitude for samples treated with 0.10 M of InCl3, but the resistivity remained in the order of 103 ohm/cm2, suggesting that the indium treatment had no considerable effect on resistivity. Hence, despite the deficit in the optical results, samples treated at 0.10 M InCl3 showed promising characteristics as well as the viability of treatment with 0.10 M InCl3 as an alternative to standard CdCl2 treatment. 2023 by the authors.